New pup on the block - Winston , Sherri; Jose , Gladys (New York, NY Harper, an imprint of HarperCollinsPublishers, 2022)
"Wednesday's brother's drone went missing in their own backyard. And that can mean only one thing--the thief is one of their friends! Can the neighborhood's newest service dog help Wednesday sniff out the bandit? Or will the case of the missing drone be a doggone disaster?"-- Provided by publisher
English stories
Keywords: Child detectives; Dogs Fiction